OTONOM SİNİR SİSTEMİ VE ANESTEZİ - (:unkn) unknown (My University, 2015)
Otonom sinir sistemi temel olarak spinal kord, beyin sap ve hipotalamusta yer alan merkezler taraf ndan aktive edilir. Homeostazisin devam ettirilmesinde önemli bir rol oynamaktad r. Efferent otonomik sinyaller vücudun çeflitli organlar na sempatik ve parasempatik sinir sistemi olarak adland r lan 2 major alt ünite taraf ndan iletilir. Her iki sistemin akti f olarak çal flmas sonucu doku aktivitesi art r l r yada inhibe edilir. Sonuçta doku fonksiyonlar n n do¤ru biçimde regülasyonu korunur. Anestezi uygulamalar nda kullan lan gerek volatil gerekse de intravenöz ajanlar sempatik ve parasempatik sistem üzerine farkl etkiler oluflturmaktad r. Bu derlemenin amac otonom sinir sistemi fizyolojisi ile anestezi prati¤inde uygulanan ilaçlar n bu sistem üzerine etkilerini gözden geçirmektir

The autonomic nervous system is principally activated by the centers located in spinal cord, brain stem and hypothalamus. It plays an important role in maintaining the homeostasis. Efferent autonomic signals are transmitted to various organs of the body by two major subunits called the sympathetic and parasympathetic nervous system. Tissue activity is increased or inhibited actively as a result of the functions of these two systems. Eventually the regulation of tissue functions is protected in a correct manner. Both volatile and intravenous agents, used in anesthesia practice, produce di fferent effects on sympathetic and parasympathetic systems. In this study we aim to review the autonomic nervous system physiology and the effects of drugs applied in anesthesia on this system.
AUTONOMIC NERVOUS SYSTEM AND ANESTHESIA
Keywords: Cerrahi